The Effects of Soy Isoflavone on Lipid Profile in Menopausal Women: A Systematic Literature Review of Randomized Controlled Trials - Nur Apriyan; Asyifa Robiatul Adawiyah; Atik Kridawati; Lili Indrawati; Sugeng Hadisaputra (Journal of Scientific Insights, 2026)
Background: The transition into menopause during the perimenopausal period causes fluctuating ovarian function and adverse lipid shifts, increasing cardiovascular disease (CVD) risks. This systematic literature review evaluates the clinical efficacy of soy isoflavone supplementation on lipid profiles in perimenopausal women, synthesizing evidence from randomized controlled trials (RCTs) only. Methods: A systematic search was conducted in PubMed, Scopus, and ProQuest through May 2026. Of the 355 initially identified records (PubMed: 11, Scopus: 309, ProQuest: 35), four RCTs evaluating perimenopausal cohorts met the strict inclusion criteria for the qualitative synthesis. The reviewed trials investigated interventions ranging from isolated soy protein to specific isoflavone extracts and multi-ingredient nutraceutical combinations. Results: The synthesized data revealed nuanced, baseline-dependent lipidemic outcomes. In healthy, normocholesterolemic perimenopausal women, soy protein or isolated isoflavone intake did not significantly modulate total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), or coagulation factors. Conversely, pronounced therapeutic benefits—characterized by significant reductions in TC, LDL-C, and triglycerides, along with improved metabolic biomarkers—were observed exclusively in perimenopausal cohorts with baseline metabolic syndrome or severe vasomotor symptoms, or when co-administered with metabolic-synergistic factors such as myo-inositol. Conclusion: Soy isoflavones do not uniformly alter lipid profiles in perimenopausal women. Their cardioprotective efficacy is heavily contingent upon baseline metabolic status, offering substantial lipid-modulating benefits for metabolically vulnerable cohorts while showing negligible effects in healthy individuals during the menopausal transition.